Rheologisch-Glaziologische Untersuchungen om Firngebeit des Grönländischen Inlandeises. - Haefeli, R.; Brandenberger, F. (Meddelelser om Grønland, 1968)
The results of the rheological-glaciological investigations, which were conducted mainly at the Jarl-Joset Station at the time of the International Glaciological Greenland Expedition in 1957- 60, are dealt with in two sections. In the first section, four chapters (1 - 4) describe the methods, apparatus and instruments used and set forth the results obtained directly by these methods of investigation. It was possible to carry out the programme, which centred on the determination of certain mechanical properties of the firn in situ (ramming resistance, shear strength, vicosity and deformation under its own weight and under artificial loading) almost in its entirety. The second section, comprising six chapters (5-10), consists of a first glaciological evaluation of individual results. It embraces among other things the viscosity properties of the relatively fluid polar firn lying above the polar ice (by comparison with the alpine winter snow cover and with the results of other investigators), the glaciological interpretation of the West-East profile and the displacement measurements (including the deformation quadrilaterals). Comparison of these latter results with the predictions based on our waking hypothesis (HAEFELI 1961) showed good agreement. A special chapter is devoted to the approximate calculation of the age of the ice. A laboratory test with a plate-gap model, system Hele-Shaw which was carried out in the Laboratory for Hydraulic Research and Soil Mechanics in Zurich , proves the correctness of the theoretically calculated streamlines and graphically demonstrates the state of motion of the inland ice. In conclusion the most important results of the investigations are summarized and a few suggestions made for the repetition mesurement.